Geographically widespread and novel hemotropic mycoplasmas and bartonellae in Mexican free-tailed bats and sympatric North American bat species - Daniel J. Becker; Kristin E. Dyer; Lauren R. Lock; Beckett L. Olbrys; Shawn A. Pladas; Anushka A. Sukhadia; Bret Demory; Juliana Maria Nunes Batista; Micaela Pineda; Nancy B. Simmons; Amanda M. Adams; Winifred F. Frick; et al. (mSphere)
ABSTRACT Bacterial pathogens remain poorly characterized in bats, especially in North America. We describe novel (and in some cases panmictic) hemoplasmas (10.1% positivity) and bartonellae (25.6% positivity) across three colonies of Mexican free-tailed bats (Tadarida brasiliensis), a partially migratory species that can seasonally travel hundreds of kilometers. Molecular analyses identified three novel Candidatus hemoplasma species most similar to another novel Candidatus species in Neotropical molossid bats. We also detected novel hemoplasmas in sympatric cave myotis (Myotis velifer) and pallid bats (Antrozous pallidus), with sequences in the latter 96.5% related to Candidatus Mycoplasma haematohominis. We identified nine Bartonella genogroups, including those in cave myotis with 96.1% similarity to Candidatus Bartonella mayotimonensis. We also detected Bartonella rochalimae in migratory Mexican free-tailed bats, representing the first report of this human pathogen in the Chiroptera. Monthly sampling of migratory Mexican free-tailed bats during their North American occupancy period also revealed significant seasonality in infection for both bacterial pathogens, with prevalence increasing following spring migration, peaking in the maternity season, and declining into fall migration. The substantial diversity and seasonality of hemoplasmas and bartonellae observed here suggest that additional longitudinal, genomic, and immunological studies in bats are warranted to inform One Health approaches.IMPORTANCEBats have been intensively sampled for viruses but remain mostly understudied for bacterial pathogens. However, bacterial pathogens can have significant impacts on both human health and bat morbidity and even mortality. Hemoplasmas and bartonellae are facultative intracellular bacteria of special interest in bats, given their high prevalence and substantial genetic diversity. Surveys have also supported plausible zoonotic transmission of these bacteria from bats to humans, including Candidatus Mycoplasma haematohominis and Candidatus Bartonella mayotimonensis. Greater characterization of these bacteria across global bat diversity (over 1,480 species) is therefore warranted to inform infection risks for both bats and humans, although little surveillance has thus far been conducted in North American bats. We here describe novel (and in some cases panmictic) hemoplasmas and bartonellae across three colonies of Mexican free-tailed bats and sympatric bat species. We find high genetic diversity and seasonality of these pathogens, including lineages closely related to human pathogens, such as Bartonella rochalimae.